Sensor Bergerak untuk Pengenalan Sumber Cahaya dalam Rangka Penghematan Energi Listrik - Santoso, Djunaidi; Goeirmanto, Leonard (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Insufficient electricity supply in Java, Indonesia, has become an critical problem to be dealt by the goverment. One solution campaigned by the government is using electricity effectively by turning off unused devices that waste electricity. To make this action as a routine needs a reminder that can help remind people continually. One example of a reminder is an automatic static sensor which is already applied in some places. Dynamic sensor is one of best method to save energy because it can warn the user to turn off unused lamps. Dynamic sensor is also called moving sensor because it is able to move from a place to another and has a wide service area. This study gives information about the use of moving sensor in some areas in order to save electricity energy. As a pilot project, the use of moving sensor needs to be improved by a further study.